Block copolymer technology applied to nanoelectronics. Issue 9 (16th August 2013) - Tallegas, Salomé; Baron, Thierry; Gay, Guillaume; Aggrafeil, Claire; Salhi, Billel; Chevolleau, Thierry; Cunge, Gilles; Bsiesy, Ahmad; Tiron, Raluca; Chevalier, Xavier; Navarro, Christophe; Aissou, Karim; et al.
Abstract For the last ten years, the authors of this paper have been actively involved in studying the self‐assembly of block copolymers for their high potential in nano‐patterns fabrication. The aim of this paper is to give an overview of this important work by focusing on the main systems, process and results that have been obtained. In the first part of this paper, it will be shown that, a bi‐layer and tri‐layer strategies to transfer a diblock copolymer pattern into the subjacent substrate have been developed. As a result, a generic CMOS compatible lift‐off strategy for transferring a block copolymer template to a semiconductor substrate is demonstrated. An aluminum oxide (Al2O3) hard mask is selectively deposited by atomic layer deposition in an organized array of holes obtained in a polystyrene (PS) matrix via polystyrene‐b‐poly(methyl methacrylate) (PS‐b ‐PMMA) self‐assembled layer. The Al2O3 nanodots act as a highly resistant mask to plasma etching, and are used to pattern high aspect ratio (> 10) silicon nanowires and nanopillars. Then, we report a synoptic methodology to optimize the long‐range order induced by graphoepitaxy of block copolymer (BCP) self‐assembly. Pre‐patterned structures used in the graphoepitaxy approach have been generated by e‐beam lithography on a commercial hydrogen silsquioxane resist. In a more prospective but promising approach, the second part of this paper focus on the study of the self‐assembly of rod‐coil amylose‐b‐polystyrene (Mal‐b‐PS) block copolymer. Interestingly, the nano‐organization of this block copolymer falls in an interdomain spacing of about 10 nm, much smaller than flexible‐flexible petrol block copolymer systems. In addition, hydrogen‐bonding interactions between carbohydrate rods (amylose) and 40, 4‐bipyridine (bipy) molecules induce phase transitions. Such kind of systems coupled with the transferring approach and graphoepitaxy strategies exposed in this paper could permit to get ultra small (<10 nm) and well‐organized patterns. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)